EFFORTS TO INCREASE STUDENT LEARNING ENTHUSIASM IN LEARNING ADDITION AND SUBTRACTION THROUGH THE ANIMATED VIDEO "ADDITON AND SUBTRACTION WITH DINOSAURS - MATH FOR KIDS - MATH OPERATIONS” - Sofyan, Fuaddilah Ali; Dinda, Adinda Dwi; Rahayu, Intan Tria; Santya, Moly; Ningsih, Lisa Septia; Eliyati, Eliyati (Jurnal Multidisipliner Kapalamada, 2022)
The use of technology in delivering learning materials is very good. As video-based learning are very helpful in learning. Because the learning videos shown are equipped with sound, images and animations that can help students be more motivated in learning. This study aims to analyze the contents of the animated video “Learn Numbers" by Dr. Panda". Student motivation in this study was viewed from the use of video lessons by educators in learning. Does the animation contain learning about mathematics? Can animation educate children? Addition and subtraction in mathematics, namely number operations, is a material for learning mathematics at the elementary school level. So far, students have only been introduced to the material taught by the teacher through the blackboard and then recorded and given assignments without knowing what was learned. So that student learning outcomes according to the low level of understanding of students. To overcome this, interactive multimedia is applied because interactive